Capacity Building and Human Resource Development Initiatives: Community Based Tourism Development in Nepal - Pandey, Rabi Jung (Nepal Tourism and Development Review, 2013)
Community Based Tourism (CBT) in Nepal is considered one of the important industries for sustainable development and empowerment. The government is apprehensive on promoting this industry with higher priority. With a view, it being an employment-oriented industry there is a notion that it could solve the socio-economic discrepancies, if expanded to many areas of the country. Taking these facts into consideration, it has been initiated to develop community-based tourism with wider objectives. It is also argued that the impacts on livelihoods and not just income need to be assessed along with the variety of positive and negative effects. There is a strong belief that CBT capacitates and empowers local people as actors in tourism planning, development and management. There is a perception among the local stakeholders that CBT helps them understand how tourism could contribute to their well-being and take active roles to minimize the negative impacts of tourism. It is intended that the management, development and ownership of local tourism resources and products should be carried out by the local communities themselves to ensure maximum tourism benefits to the local stakeholders, making them more responsible. Despite the fact that there are numerous training courses being run particularly focused on the tourism development in Nepal, there is still a deficiency of more CBT related training manuals. Effective teaching and learning process, sharing knowledge and experiences amongst the trainers, participants as well as other stakeholders are still in high demand. Furthermore, proper monitoring and follow-up practices of executed training events are preferred to be ensured. DOI: http://dx.doi.org/10.3126/ntdr.v1i1.7373 Nepal Tourism and Development Review Vol.1(1) 2011 83-101